2020
DOI: 10.1177/1468087420961211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impacts of combustion chamber bowl geometry and injection timing on a reactivity controlled compression ignition engine at low and high load conditions

Abstract: The present paper aims to assess the impacts of diesel injection timing and two bowl geometries including re-entrant and wide-shallow combustion chambers on the combustion characteristics, emissions formation, and fuel consumption in a reactivity controlled compression ignition diesel engine under low and high load (five and nine bar indicating mean effective pressure) conditions. The results revealed that diesel injection at −60 CA ATDC under low load conditions significantly decreased soot and NOx emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Since it is difficult to achieve compression ignition for hydrogen, a highly reactive fuel is required to assist the ignition of hydrogen for CI engines. Currently, the dual-fuel combustion mode of reactivity controlled compression ignition (RCCI) 15,16 has been extensively investigated, and it can flexibly adjust the ignition timing and heat release processes by controlling the fuel reactivity and injection timing in the cylinder. 17 Previous studies indicated that high thermal efficiency, low emissions, and wide load expansion could be achieved for RCCI combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is difficult to achieve compression ignition for hydrogen, a highly reactive fuel is required to assist the ignition of hydrogen for CI engines. Currently, the dual-fuel combustion mode of reactivity controlled compression ignition (RCCI) 15,16 has been extensively investigated, and it can flexibly adjust the ignition timing and heat release processes by controlling the fuel reactivity and injection timing in the cylinder. 17 Previous studies indicated that high thermal efficiency, low emissions, and wide load expansion could be achieved for RCCI combustion.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 New low temperature combustion (LTC) modes such as HCCI or reactivity controlled compression ignition (RCCI) aim to emit low NOx and low soot concentration thanks to longer ignition delays. [27][28][29] They are nevertheless limited by their MPRR levels due to the rapid auto-ignition of the mixture [30][31][32] and use to exhibit high resonance excitation. 33 Similar to knock in SI engines, the resulting pressure waves represent a source of potential damage for the engine and must be limited and controlled.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, the application of HCCI to commercial engines has been proven to be very difficult owing to the challenge of combustion phasing control and high peak pressure rise rate (PPRR) at high loads. Several improved strategies, such as fuel stratified combustion, 58 partially premixed combustion (PPC), 912 and reactivity-controlled compression ignition (RCCI), 1316 have been developed to regulate the combustion process by applying the direct injection (DI) of fuel into the cylinder.…”
Section: Introductionmentioning
confidence: 99%